Criteria For Choosing of a Life Partner with the War Situation in Syria (A Field Study in Damascus City) (Damascus University Journal of arts and humanities sciences, 2021)
The current research aims to identify the preferred criteria in choosing a life partner from the youth point of view in the circumstances of the war in Syria.               An appropriate methodology was adopted for the purpose of this research, namely, the descriptive analytical method, and social survey by sample and the questionnaire was also used as a tool to collect field data. The original community of research will be youth with Syrian nationality (male and female) aged between 20- 30 years and residents of Damascus during the research period. The sample size, which was taken according to the method of random sampling and randomization was 160 (80 of them males and 80 of them females).                                         On the statistical analysis of the data carried out through the statistical program (SPSS) using percentages, a number of results were found indicating the negative impact of the war on Syria in most sample units (displacement, lack of work, low standard of living, living in rented houses); as well as their impact on some criteria of marital selection among young people.
Keywords: Criteria For Choosing of a Life Partner; The War on Syria; Youth